2005
DOI: 10.1111/j.1463-6409.2005.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of the globally distributed freshwater prawn genus Macrobrachium (Crustacea: Decapoda: Palaemonidae): biogeography, taxonomy and the convergent evolution of abbreviated larval development

Abstract: There has hitherto been little research into evolutionary and taxonomic relationships amongst species of the freshwater prawn genus Macrobrachium Bate across its global distribution. Previous work by the authors demonstrated that the endemic Australian species did not evolve from a single ancestral lineage. To examine whether other regional Macrobrachium faunas also reflect this pattern of multiple origins, the phylogeny of 30 Macrobrachium species from Asia, Central/South America and Australia was inferred fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
115
0
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(133 citation statements)
references
References 50 publications
6
115
0
12
Order By: Relevance
“…Murphy & Austin (2005) found that the presence of abbreviated development in a large set of Macrobrachium species did not have any relation to the phylogeny of the group, indicating a widespread convergence to solve the problems imposed by the freshwater habitat. In the present contribution this widespread convergence is extended to include species from another five genera, all of which display large eggs and abbreviated development.…”
Section: Discussionmentioning
confidence: 96%
“…Murphy & Austin (2005) found that the presence of abbreviated development in a large set of Macrobrachium species did not have any relation to the phylogeny of the group, indicating a widespread convergence to solve the problems imposed by the freshwater habitat. In the present contribution this widespread convergence is extended to include species from another five genera, all of which display large eggs and abbreviated development.…”
Section: Discussionmentioning
confidence: 96%
“…The response may also be called a hypo-conformation, as in Moreira et al (1983) for M.acanthurus and other species of the genus. This strong tolerance to increases in salinity is in fact expected from the components of a clade that has invaded the freshwater relatively recently (Murphy and Austin 2005, Augusto et al 2007a, b, 2009, Pileggi and Mantelatto 2010, Collins et al 2011, McNamara and Faria 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Palaemonid shrimps also follow this pattern (Freire et al 2003, Murphy and Austin 2005, Augusto et al 2009, Boudour-Boucheker et al 2013. It is during ecdysis that cell volume may be challenged in these shrimps, as their internal medium fluctuates (compared to the intermoult period), diluting strongly in fresh waters.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…data). Since both traits resemble those of estuarine shrimp larvae, and a coastal marine origin is generally accepted for limnic palaemonids (Walker 1992, Jalihal et al 1993, Anger 2001, Murphy & Austin 2005, they may be explained as phylogenetic relics that have persisted from the ancestral clade.Palaeogeographic and palaeoecological evidence for marine incursions during the early and middle Miocene (Lovejoy et al 1998(Lovejoy et al , 2006 suggests that the ancestors of Macrobrachium amazonicum may first have migrated from the Caribbean coast into western Amazonian inland waters, where brackish conditions prevailed. The invaders subsequently spread over an expanding, interconnected, and increasingly limnic subandine lake system that was formed due to the Andean orogenesis (Räsänen et al 1990, Hoorn et al 1995, Wesselingh et al 2002, gradually adapting to fresh water.…”
mentioning
confidence: 99%